Multiscale variation analysis of sea surface temperature in the fishing grounds of pelagic fisheries - Qixiang Lai; Qixiang Lai; Weifeng Zhou (Frontiers in Marine Science)
Sea surface temperature (SST) are the focus of attention in global climate discussion. In particular, for pelagic fisheries that depend on the marine environment, understanding and mastering changes in SST is of great significance for managing fisheries resources to promote their sustainability. Multiscale variation analysis of SST from 1982 to 2021 has been done in this paper concerning the main eight fishing grounds of pelagic fisheries using the Optimum Interpolation Sea Surface Temperature(OISST) released by NOAA. The mean, incremental quantity, standard deviation, and overall mean standard deviation of SST per decade in these eight fishing grounds are calculated. Fast Fourier Transform, STL decomposition, and PELT of change point detection method are used get the trends and fluctuations of SST by obtaining the metrics, such as seasonal intensity indices, cycles, and change points. The study results show that: ① Over the past 40 years according to the average SST per 10 years, the main fishing grounds worldwide have warmed significantly. The cumulative warming of the fishing grounds in the northwest Pacific and the western Pacific is most obvious. However, except for the northwest Pacific, the increase of the average SST in the last 10 years is higher than in the previous 10 years in all areas. Among them, there are 5 regions which increase of the average SST in the last 10 years is higher than in the previous 2 decades, while the central Atlantic and the eastern Indian Ocean showed that the most significant increases of the average SST take place in the period from 1992 to 2001. ② From the standard deviation, and overall mean standard deviation of SST per decade, the West Pacific and the Northwest Pacific have the most significant long-term and short-term fluctuations. ③ The two regions with the highest seasonal intensity index are the northwest Pacific and the eastern Indian Ocean. ④ 1987, 1997, 2001, 2007, 2012, and 2017 were years in which change points occurred. However, except in the Indian Ocean, the number of change points and the years they occurred were inconsistent in the oceans.